Evaluasi Nilai Volume Produksi Overburden di PT Ansaf Inti Resources Site Berambai Bulan September 2022 - Muhammad Havit Pratama; Dawamul Arifin; Radik Khairil Insanu; Nia Kurniadin (Politeknik Pertanian Negeri Samarinda, 2023)
PT. Ansaf Inti Resources is located in Kec. Kutai Kartanegara, East Kalimantan. The coal mining process is preceded by excavation of overburden or activities carried out prior to coal getting to meet its production target, in determining the volume of overburden stripping in the Alam 4 pit survey activities are carried out and the determination of the rate of conveyance. In survey activities carried out by measuring the coordinates of X/easting, Y/northing and Z/elevation. The purpose of conducting research on,